Writing the Torn Body: Ars Poetica, Violence, and Resistance in Hila Lahav “Till Morning” - Carandina, Elisa (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2024)
The artistic production of several contemporary Hebrew-language women poets manifests a privileged concern with the body and its expressive capacities. In this context, the work of Hila Lahav is particularly significant, as it develops a poetics in which the body becomes both the subject and the medium of artistic creation. Focusing on Hila Lahav’s collection ‘Ad Ha-boqer’ (Till Morning), this article examines how her writing articulates an Ars poetica rooted in the fragmented, wounded body as a site of resistance to violence and silence. Through the figure of the unnamed wife in Judges 19 and the recurrent imagery of skin, dismemberment, and metamorphosis, Hila Lahav’s poems reconfigure abjection, mourning, and vulnerability as the conditions of a speaking body rather than a mute corpse. By reading Till Morning alongside biblical exegesis and feminist criticism, the article traces how Lahav’s poetic voice “writes its own name” on and through the body, elaborating a corporeal practice of memory and testimony that refuses both erasure and voyeuristic representations of sexual violence.The article was originally published in Italian under the title “Io sono il corpo che è stato strappato al corpo”: ars poetica come pratica di resistenza nella produzione poetica di Hila Lahav, in the journal « Le forme e la storia », XV, 1-2, pp. 439-450, 2022. It is published here with the permission of the author and original publisher.